1997
DOI: 10.1111/j.1365-2044.1997.83-az0081.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphine blood concentrations in elderly postoperative patients following administration via an indwelling subcutaneous cannula

Abstract: SummaryThe pharmacokinetics of morphine in venous blood after a 5 mg bolus dose via an indwelling subcutaneous cannula were characterised in 22 elderly patients undergoing elective major surgery. In a subgroup of seven patients, the kinetics were also characterised after a second 5 mg dose of morphine administered 180 min after the first dose. Blood morphine concentrations following the single dose were highly variable -the coefficients of variation of C max , T max and the AUC up to 180 min (AUC 180 ) were 54… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The common perception that subcutaneous diamorphine is absorbed slowly and erratically may be attributed to early clinical experiences with military casualties and hypovolaemia ( Semple et al. 1997 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The common perception that subcutaneous diamorphine is absorbed slowly and erratically may be attributed to early clinical experiences with military casualties and hypovolaemia ( Semple et al. 1997 ).…”
Section: Discussionmentioning
confidence: 99%
“…The common perception that subcutaneous diamorphine is absorbed slowly and erratically may be attributed to early clinical experiences with military casualties and hypovolaemia (Semple et al 1997). Contemporary anaesthetic and recovery management results in patients being discharged from recovery with body temperature and¯uid balance within the normal range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gades et al (24) conducted a study in mice and stated that sc morphine showed peak analgesic effect within 2-3 hours and that dose interval was 2-3 hours. Semple et al (25) reported that peak serum morphine concentration was achieved in 16±7 minutes after subcutaneous administration. Administration of sc morphine provides earlier postoperative pain control as compared to intramuscular (im) administration; because morphine reaches to peak plasma concentration in 17.5-27.8 minutes after im administration (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…To the contrary, it is a popular route of administration for the management of chronic conditions, such as cancer pain [46].…”
Section: Subcutaneousmentioning
confidence: 99%